“I Have Some Sense of Loss but More Sense of Self”: A Qualitative Content Analysis of Chinese University Emerging Adults’ Personal Life Stories - Chen, Hua; Wang, Ying; Liu, Zengmei (Frontiers in Psychology, 2021)
The longitudinal, qualitative study aimed to explore the lived experiences of Chinese university emerging adults by analyzing their personal life stories, reflective journals, and semi-structured interview data collected over a two-year period. A qualitative content analysis was used to identify five themes: maturity, academic performance, interpersonal communication skills, social support network, and sense of loss. The study found that the growth in emerging adulthood was dynamic, positive, and multifaceted. The study demonstrated that writing personal life stories, as a practice of meaningful literacy instruction in EFL contexts, helped students to record a memorable past, reconcile with the past, and strive for personal growth. These findings suggest that emerging adults’ personal growth be stressed in foreign language teaching to promote Chinese university emerging adults’ growth and development. It is also suggested that personal life stories be used in foreign language teaching under the guidance of meaningful literacy instruction.